Implementation Of The Dimensions Of Faith, Fear Of God And Noble Characters In The Project (P5) - Angeli, Reta (Childhood Education : Jurnal Pendidikan Anak Usia Dini, 2025)
The Pancasila Student Profile Strengthening Project is a curriculum improvement effort that aims to instill moral and religious values in early childhood. This research aims to determine the implementation of the dimensions of faith, piety to God Almighty, and noble character in the Pancasila Student Profile Strengthening Project. The research was conducted at Kindergarten Negeri Pembina 4 Palembang with the research subjects being children in class B3. The research method used is a qualitative type of research with a phenomenological approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusions. The results of the study showed that the implementation of the dimensions of faith, piety to God Almighty, and noble character in the Pancasila Student Profile Strengthening Project at Kindergarten Negeri Pembina 4 Palembang has been running very well. This can be seen from the elements in these dimensions, namely religious morals, personal morals, morals to humans, morals to nature, and state morals that have been instilled in the children's character. Then there are supporting and inhibiting factors, namely the cooperation of enthusiastic parents and teachers, as well as the enthusiasm of the children in carrying out activities. As for the inhibiting factor, namely the lack of teacher understanding of the Pancasila Student Profile. However, this can be overcome by providing training on the Pancasila Student Profile by the principal to improve teacher understanding.